2021
DOI: 10.1002/cssc.202102107
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Fuels from Biomass: Photocatalytic Hydrodecarboxylation of Octanoic Acid by Ni Nanoparticles Deposited on TiO2

Abstract: Decarboxylation of low‐value fatty acids from biomass is a simple process to produce synthetic fuels suitable to be blended with gasoline or diesel. The present study reports the photocatalytic decarboxylation of octanoic acid in the presence of H2 by a series of modified TiO2 to form mixtures of n‐heptane and tetradecane as major products in variable proportions, depending on the photocatalyst and the reaction conditions. It was found that the photocatalytic activity increases upon an optimal reductive NaBH4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…28 Recently, Hu et al employed a 10% Ni/TiO 2 photocatalyst for the decarboxylative hydrogenation of n-octanoic acid, resulting in the production of up to 20% of the coupling product under a hydrogen pressure of 0.2 MPa. 19 It has been established that through the decarboxylation process on TiO 2 , fatty acids can be transformed into active alkyl radicals, 29−31 to hydrogenation, coupling, disproportionation, or oxidation reactions, leading to a series of byproducts. 10,32−36 Manley et al studied the homocoupling of free radicals after photocatalytic decarboxylation of carboxylic acids and found that the yield was greatly affected by the substrate, indicating that the reactivity of free radical species in this system is uncontrollable.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, Hu et al employed a 10% Ni/TiO 2 photocatalyst for the decarboxylative hydrogenation of n-octanoic acid, resulting in the production of up to 20% of the coupling product under a hydrogen pressure of 0.2 MPa. 19 It has been established that through the decarboxylation process on TiO 2 , fatty acids can be transformed into active alkyl radicals, 29−31 to hydrogenation, coupling, disproportionation, or oxidation reactions, leading to a series of byproducts. 10,32−36 Manley et al studied the homocoupling of free radicals after photocatalytic decarboxylation of carboxylic acids and found that the yield was greatly affected by the substrate, indicating that the reactivity of free radical species in this system is uncontrollable.…”
Section: Introductionmentioning
confidence: 99%
“…Among the options to avoid the harsh conditions applied by conventional routes to produce biofuels, photocatalytic hydrodecarboxylation of bioderived fatty acids has emerged as a viable alternative to afford hydrocarbons chemically compatible with drop‐in biofuels under mild reaction conditions. For example, alkanes in the range of synthetic fuels were obtained from fatty acids in high yields and high selectivity via photodecarboxylation using Pt/TiO 2 or Ni/TiO 2 as the photoredox catalyst system under UV light irradiation [18,19] . Although a major improvement to traditional protocols, the developed conditions still rely on the use of an atmosphere of hydrogen gas to promote the efficient termination of the active alkyl radical, rendering this approach less appealing.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxylic acid photodecarboxylation requires the development of efficient photocatalysts, and considerable research has been conducted in this area trying to find more suitable materials. ,, In a semiconducting photocatalyst, photon absorption promotes electrons from the valence band to the conduction band, generating an electron hole in the valence band. This elementary process generates a transient charge separated state with negative electrons (e – ) and positive holes (h + ) pairs .…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 , having a bandgap of about 3.4 eV, absorbs photons of wavelength shorter than 380 nm, but other semiconductors with narrower bandgap can be excited by visible light. , TiO 2 possesses several advantages, including high activity under UV irradiation, high chemical and photochemical stability against photocorrosion, high relative abundance, low toxicity, and large scale affordability. These advantages have motivated the interest for TiO 2 in photocatalytic processes such as solar fuels production, , environmental remediation, , and photodecarboxylation. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation